Incidence of morbidity and mortality in neonate born to mothers with premature rupture of membranes - Lokhande, Sumant; Nistane, Rajendra (International Journal of Contemporary Pediatrics, 2016)
Background:Preterm premature rupture of membranes (PPROM) refers to PROM prior to 37 weeks of gestation. Premature rupture of membranes (PROM) is one of the most common problems in obstetrics complicating approximately 5-10% of term pregnancies. The objective of this study was to know the incidence of early onset sepsis following PROM (premature rupture of membranes) more than 18 hours, mortality among neonates born to mothers with PROM more than 18 hours. Methods: The study was conducted in department of pediatrics, Dr. Panjabrao Deshmukh memorial medical college and hospital, Amravati. All neonates born to healthy mothers with PROM more than 18 hours during their hospital stay were studied. An allowable error sample size of 60 was calculated. Detailed birth history including resuscitation details, APGAR score and gestational age assessment were evaluated. In examination of the neonate, the pulse, respiratory rate, CFT and temperature were noted followed by systemic examination. Required investigations were done for the neonate and were followed during their hospital stay. All the details were fed into the preformed teacher-made proforma. Results:51.7% of the neonates were males and 48.3% were females. 65% of the total neonates were born by normal vaginal delivery and 35% were delivered by caesarean section. 53.3% of the cases had premature rupture of membranes of 18 - <24 hours duration, 38.3% cases had premature rupture of membranes of 24 to 72 hours and 8.3% cases had premature rupture of membranes of more than 72 hours. RDS was the most common clinical manifestation (36.7%) followed by septicemia (8.3%), meningitis (1.7%) and pneumonia (1.7%). Conclusions:Premature rupture of membranes is a high-risk obstetric condition. Active management is needed to enable delivery within 24 hours of premature rupture of membranes as it offers better neonatal outcome. Morbidity increases as the duration of premature rupture of membranes increases. The incidence of neonatal infection in neonates born to mothers with PROM was 8.3%. CRP was positive in 30% of cases. Out of 60 cases 1.7% had leucopenia and 18.3% had leucocytosis. Most common organisms isolated in blood culture were staphylococcus followed by Klebsiella, E. coli, pseudomonas and coagulase negative Staphylococci.